Safety, tolerability, and clinical and neural effects of single-dose psilocybin in obsessive–compulsive disorder: protocol for a randomized, double-blind, placebo-controlled, non-crossover trial - Ching, Terence H. W.; Grazioplene, Rachael; Bohner, Calvin; Kichuk, Stephen A.; DePalmer, Giuliana; D’Amico, Elizabeth; Eilbott, Jeffrey; Jankovsky, Anastasia; Burke, Michelle; Hokanson, Jamila; Martins, Brad; Witherow, Chelsea; et al. (Frontiers in Psychiatry, 2023)
Background Psilocybin may help treat obsessive–compulsive disorder (OCD). To date, only one open-label study of psilocybin for OCD exists, necessitating further investigation with a randomized controlled design. The neural correlates of psilocybin’s effects on OCD have also not been studied. Objectives This first-of-its-kind trial aims to evaluate the feasibility, safety, and tolerability of psilocybin in the treatment of OCD, provide preliminary evidence on the effects of psilocybin on OCD symptoms, and elucidate neural mechanisms that may mediate psilocybin’s effects on OCD. Design We use a randomized (1:1), double-blind, placebo-controlled, non-crossover design to examine the clinical and neural effects of either a single dose of oral psilocybin (0.25 mg/kg) or active placebo-control agent (250 mg of niacin) on OCD symptoms. Methods and analysis We are enrolling 30 adult participants at a single site in Connecticut, USA who have failed at least one trial of standard care treatment (medication/psychotherapy) for OCD. All participants will also receive unstructured, non-directive psychological support during visits. Aside from safety, primary outcomes include OCD symptoms over the past 24 h, assessed by the Acute Yale-Brown Obsessive–Compulsive Scale and Visual Analog Scale ratings. These are collected by blinded, independent raters at baseline and the primary endpoint of 48 h post-dosing. Total follow-up is 12 weeks post-dosing. Resting state neuroimaging data will be collected at baseline and primary endpoint. Participants randomized to placebo will be offered the chance to return for an open-label dose of 0.25 mg/kg. Ethics statement All participants will be required to provide written informed consent. The trial (protocol v. 5.2) was approved by the institutional review board (HIC #2000020355) and registered with ClinicalTrials.gov (NCT03356483). Discussion This study may represent an advance in our ability to treat refractory OCD, and pave the way for future studies of neurobiological mechanisms of OCD that may respond to psilocybin.